Green Synthesis of Hexagonal Silver Nanoparticles Using a Novel Microalgae Coelastrella aeroterrestrica Strain BA_Chlo4 and Resulting Anticancer, Antibacterial, and Antioxidant Activities - Reham Samir Hamida; Mohamed Abdelaal Ali; Zakiah Nasser Almohawes; Hadil Alahdal; Maha Abdullah Momenah; Mashael Mohammed Bin-Meferij (MDPI AG, 2022)
Microalgae-mediated synthesis of nanoparticles (NPs) is an emerging nanobiotechnology that utilizes the biomolecular corona of microalgae as reducing and capping agents for NP fabrication. This study screened a novel microalgal strain for its potential to synthesize silver (Ag)-NPs and then assayed the biological activities of the NPs. Coelastrella aeroterrestrica strain BA_Chlo4 was isolated, purified, and morphologically and molecularly identified. Chemical composition of the algal extract was determined by GC-MS analysis. Ag-NPs were biosynthesized by C. aeroterrestrica BA_Chlo4 (C@Ag-NPs) and characterized using various techniques. Antiproliferative activity and the biocidal effect of C@Ag-NPs, C. aeroterrestrica algal extract, and chemically synthesized Ag-NPs (Ch@Ag-NPs) were explored, and the scavenging activity of C@Ag-NPs against free radicals was investigated. C@Ag-NPs were hexagonal, with a nanosize diameter of 14.5 ± 0.5 nm and a maximum wavelength at 404.5 nm. FTIR and GC-MS analysis demonstrated that proteins and polysaccharide acted as capping and reducing agents for C@Ag-NPs. X-ray diffraction, energy diffraction X-ray, and mapping confirmed the crystallinity and natural structure of C@Ag-NPs. The hydrodynamic diameter and charge of C@Ag-NPs was 28.5 nm and −33 mV, respectively. C@Ag-NPs showed significant anticancer activity towards malignant cells, with low toxicity against non-cancerous cells. In addition, C@Ag-NPs exhibited greater antioxidant activity and inhibitory effects against Gram-positive and -negative bacteria compared with the other tested treatments. These findings demonstrate, for first time, the potential of a novel strain of C. aeroterrestrica to synthesize Ag-NPs and the potent antioxidant, anticancer, and biocidal activities of these NPs.